2022
DOI: 10.1038/s41598-022-15280-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lime and oxalic acid on antioxidant enzymes and active components of Panax notoginseng under cadmium stress

Abstract: Cadmium (Cd) pollution poses potential safety risks for Panax notoginseng cultivation, a medicinal plant in Yunnan. Under exogenous Cd stress, field experiments were conducted to understand the effects of lime (0, 750, 2250 and 3750 kg hm−2) applied and oxalic acid (0, 0.1 and 0.2 mol L−1) leaves sprayed on Cd accumulation, antioxidant system and medicinal components of P. notoginseng. The results showed that Lime and foliar spray of oxalic acid were able to elevate Ca2+ and alleviate Cd2+ toxicity in P. notog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Pan et al. (2015) reported that the addition of oxalate could improve the accumulation of saponins in Psammosilene tunicoides cell suspensions, and Li et al. (2022a) reported that the application of oxalate could improve the accumulation of PNSs under Cd stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pan et al. (2015) reported that the addition of oxalate could improve the accumulation of saponins in Psammosilene tunicoides cell suspensions, and Li et al. (2022a) reported that the application of oxalate could improve the accumulation of PNSs under Cd stress.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the oxalate content in the stems and roots of P. notoginseng increased significantly after leucine application (Figure 4). Pan et al (2015) reported that the addition of oxalate could improve the accumulation of saponins in Psammosilene tunicoides cell suspensions, and Li et al (2022a) reported that the application of oxalate could improve the accumulation of PNSs under Cd stress. It is thus suggested that the increase in oxalate content after leucine application may also contribute to the accumulation of PNSs.…”
Section: Leucine Increases Pnss Accumulation By Alleviating Heat Stressmentioning
confidence: 99%
“…The efficacy of P. notoginseng is affected by toxic metal contamination, a topic of increasing interest because of the abundance of mineral resources in P. notoginseng-cultivated soil. Cadmium (Cd) absorption and enrichment in P. notoginseng is relatively strong, and Cd is more easily transferred to the ground [3]. Cd contamination not only reduces the yield of P. notoginseng and diminishes the accumulation of bioactive compounds [4], but it also poses risks to environmental pollution and human health [5].…”
Section: Introductionmentioning
confidence: 99%